A new species of Schendylops Cook, 1899 from a high plateau of the Córdoba mountains (central Argentina), with notes on other Neotropical members of the genus (Myriapoda: Chilopoda: Geophilomorpha) - Pereira, Luis Alberto (2008)
Schendylops achalensis sp. n. (Chilopoda: Geophilomorpha: Schendylidae) is here described and illustrated from a female (holotype) and a male (paratype) from Pampa de Achala plateau, Córdoba mountains (central Argentina). Th e new species is characterized by having well defi ned pore fi elds on the sterna of the anterior and posterior region of the body, but totally absent on the intermediate ones, this character being shared by only four other Neotropical species of the genus, i.e., Schendylops demangei (Pereira, 1981), Schendylops demartini (Pereira & Minelli, 1996), and Schendylops placcii (Pereira & Minelli, 1996) from Argentina, and Schendylops minutus (Pereira & Minelli, 1993) from Venezuela, with which it is here compared in detail. New diagnoses for these latter species are also given.